2020
DOI: 10.6028/nist.tn.2086
|View full text |Cite
|
Sign up to set email alerts
|

A review of social media use during disaster response and recovery phases

Abstract: Under the National Construction Safety Team Act, the National Institute of Standards and Technology (NIST) investigated the May 22, 2011 tornado in Joplin, Missouri. The investigation was an effort to characterize (1) the wind environment and technical conditions associated with fatalities and injuries, (2) the performance of emergency communications systems and the public response to such communications, and (3) the performance of residential, commercial, and critical buildings, designated safe areas in build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The real-time publishing of information on these platforms means that in disaster situations users act as human sensors, detecting and documenting events. Social Media has already been implemented to detect and predict aspects of influenza spread [13], social unrest [14,20], polling and election election outcomes [21], mental illness [22] and addiction [23], as well as general natural disasters [11,24] and finally wildfires [8,25]. Studies related to disaster scenarios have revealed interesting results, building on the concept of the human sensor to inform decision making and recovery in these situations.…”
Section: The Human Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The real-time publishing of information on these platforms means that in disaster situations users act as human sensors, detecting and documenting events. Social Media has already been implemented to detect and predict aspects of influenza spread [13], social unrest [14,20], polling and election election outcomes [21], mental illness [22] and addiction [23], as well as general natural disasters [11,24] and finally wildfires [8,25]. Studies related to disaster scenarios have revealed interesting results, building on the concept of the human sensor to inform decision making and recovery in these situations.…”
Section: The Human Sensormentioning
confidence: 99%
“…(C) We train models which accurately predict attributes of the novel dataset. Accurate modelling social media sentiment during disasters may help disaster management and recovery crews make more informed, quick, data-driven decisions [11,17,24,26,33]. This is a key aspect of wildfire modelling which needs improvement, and could help fire suppression and reduce public danger.…”
Section: Sentimental Wildfire: Overviewmentioning
confidence: 99%
“…In humanitarian logistics and disaster management, typical decision-making problems rely on the humanitarian logistics operations associated with the disaster life cycle, or disaster management cycle, which is a framework popularly utilised in disaster management to understand, visualise and delineate the distinct stages of a developing disaster event. 'Its main purpose is to tie the temporal dimension of an emergency with the appropriate functions for its successful management' (Young et al 2020). Diverse authors summarise the disaster management cycle in two phases only (e.g.…”
Section: Optimisation and Decision-making In Humanitarian Logisticsmentioning
confidence: 99%
“…A review capturing the strengths and weaknesses of the literature on disaster mental health monitoring via social media is both pertinent and timely, given the availability of social media analytic tools and the current COVID-19 crisis [ 9 ]. Previous reviews [ 10 , 11 ] have taken a narrower focus by examining the health literature; however, substantial research has been published in other interdisciplinary areas [ 12 ]. Notably, research from computer science and engineering is particularly relevant, and may offer sophisticated methodological advances to address challenges specific to large, unstructured data sets obtained from social media to indicate mental health outcomes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%